Mitochondrial permeability transition induced by the anticancer drug etoposide - Custódio, J. B. A. (2001)
Etoposide (VP-16) is widely used for the treatment of several forms of cancer. The cytotoxicity of VP-16 has been assigned to the induction of apoptotic cell death but the signaling pathway for VP-16-induced apoptosis is essentially unknown. There is some evidence that this process depends on events associated with the loss of mitochondrial membrane potential ([Delta][Psi]) and/or release of apoptogenic factors, putatively as a consequence of mitochondrial permeability transition (MPT) induction. This work evaluates the interference of VP-16 with MPT in vitro, which is characterized by the Ca2+-dependent depolarization of [Delta][Psi], the release of matrix Ca2+ and by extensive swelling of mitochondria. [Delta][Psi] depolarization and Ca2+ release were measured with ion-selective electrodes, and mitochondrial swelling was monitored spectrophotometrically. Incubation of rat liver mitochondria with VP-16 results in a concentration-dependent induction of MPT, evidenced by an increased sensitivity to Ca2+-induced swelling, depolarization of [Delta][Psi], Ca2+ release by mitochondria and stimulation of state 4 oxygen consumption. All of these effects are prevented by preincubating the mitochondria with cyclosporine A, a potent and specific inhibitor of the MPT. Therefore, VP-16 increases the sensitivity of isolated mitochondria to the Ca2+-dependent induction of the MPT. Together, these data provide a possible mechanistic explanation for the previously reported effects of VP-16 on apoptosis induction.